Analytical and experimental determination of the failure-critical pressure of pipe structures manufactured by PBF-LB/M - Koers, Thorsten; Magyar, Balázs; Bödger, Christian; Tröster, Thomas (International Journal of Pressure Vessels and Piping)
The state of the art shows that PBF-LB/M offers great potential for pressure-loaded parts, with significant weight reductions and simultaneous optimization of flow resistance. This study is aimed at applying existing calculation methods for pressure-loaded parts to additively manufactured pipe structures, considering the two materials EN AC-43000 (3.2381, AlSi10Mg) and AISI 316L (1.4404, X2CrNiMo17-12-2). For this purpose, systematic tensile tests are carried out for both materials. In addition, a statistical evaluation is performed to determine the design-relevant strength characteristics with a survival probability Ps of 97.5 % for both materials in the as-built and heat-treated condition. Pipe specimens are manufactured, half of which are heat treated, geometrically measured and then subjected to a burst pressure test to experimentally determine the failure-critical internal pressure. These results are compared with calculated burst pressures. The calculations are based on the application-relevant methods identified in this study, considering the strength values determined for the respective material condition. This comparison is used to assess the suitability of the calculation methods for additively manufactured pipe structures, based on the materials investigated.
Keywords: PBF-LB/M; Pipe structures; Strength assessment; Burst pressure test; Geometrical deviations

Moderne Städte- und Gemeindepartnerschaften. Fördermöglichkeiten und Praxistrends - Marchetti, Andreas

Tagungsbericht: Von widerständigen Verweigerungen und vom (Über-)Leben in feindlichen Umgebungen. Politische Theorie zwischen (Un)Sichtbarkeiten - Althoff, Sebastian; Verhoeven, Ragna

»Inspiration & Planung« am Computer. Virtuelles Wohnen mit dem IVAR Planer - Cyrkel, Jakob (ComputerWohnen. Zur Geschichte des Computers in Wohnumgebungen zwischen Arbeit und Assistenz)
Der Beitrag konzentriert sich am Beispiel des IVAR Planers auf die virtuellen Einrichtungstools des Einrichtungskonzerns IKEA und fragt danach, welche Politiken des Wohnens und Einrichtens sich aus der Medialität dieser virtuellen Umgebungen ergeben. Anhand von Stefan Riegers Überlegungen zum virtuellen Testen werden diese Planungstools einerseits als auf Dauer gestellte Testumgebungen verstanden, die es den Kund*innen erlauben, das eigene Zuhause – ökologisch wie ökonomisch niederschwellig – virtuell immer wieder einzurichten. Andererseits werden die Anrufungen zur Kreativität, die ständig an die Kund*innen gerichtet werden, in die Überlegungen mit einbezogen, weil sich daraus eine paradoxe Konstellation ergibt: Zum einen sollen so die virtuellen Einrichtungstools kreatives Potenzial und eigenständige Gestaltung aufrufen; zum anderen werden diese Aufrufe aber durch die Medialität der Tools eingehegt und damit zu einem Steuerungsregime.

ComputerWohnen. Zur Geschichte des Computers in Wohnumgebungen zwischen Arbeit und Assistenz
Unter welchen historischen Bedingungen und mit welchen Auswirkungen wurde der Computer zum Bestandteil des Wohnalltags? Und wie verhält es sich dabei mit Praktiken des Wohnens und Wohnungseinrichtens? Die Beiträger*innen werfen einen Blick auf die Computerisierung des Zuhauses und zeigen, wie sie sich vollzieht. Der Fokus ihrer Analysen liegt einerseits darauf, wie Arbeit und Assistenz das Wohnen im Hinblick auf den Computer prägen. Andererseits denken sie den Computer aus der Perspektive der Wohnumgebungen neu und geben so einen kompakten medienhistorischen Überblick über den Beginn des Smart Homes.
Keywords: Mediengeschichte; Digitale Medien; Design; Medien; Medienwissenschaft; Medienästhetik; Mediensoziologie; Medientheorie; Medienphilosophie; Architektur; Technikgeschichte; Technik; Kultur; Kulturwissenschaft; Kulturgeschichte; Kulturtheorie; Popkultur; Geschichte des 20. Jahrhunderts; Geschichtswissenschaft; Kultursoziologie; Gender Studies; Mode; Klang; Cultural Studies; Informatik

Interfacial Softening and Electrolyte Uptake in Co3O4 OER Catalysts: Insight from Operando Spectroscopy and Fast EQCM‐D - Leppin, Christian; Placke‐Yan, Carsten; Bendt, Georg; Hernandez, Sheila; Tschulik, Kristina; Schulz, Stephan; Linnemann, Julia (ChemCatChem)
Cobalt spinel (Co3O4) catalysts are widely studied in scope of the electrocatalytic oxygen evolution reaction (OER), yet the role of interfacial structural transformation under anodic bias remains under debate. Here, we employ an operando approach, combining a fast electrochemical quartz crystal microbalance with dissipation monitoring (EQCM-D), electrochemical impedance spectroscopy (EIS), and Raman spectroscopy to investigate interfacial transformations of Co3O4 nanoparticle electrodes in alkaline electrolyte. We identify two distinct regimes during the anodic sweep prior to the macroscopic OER onset. At lower potentials, the catalyst interface remains mechanically rigid while reversibly associating several OH−/H2O species per oxidized cobalt site. At higher potentials, pronounced softening of the interface occurs alongside further uptake of electrolyte species. This indicates amorphization and a ‘swelling process’ beyond simple adsorption. Notably, an electrochemical conditioning treatment can suppress mass and compliance hysteresis without affecting OER activity, suggesting that most incorporated electrolyte species do not participate in the OER. EIS further reveals that OER intermediates form well below the apparent OER onset potential. These results advance our mechanistic understanding of interfacial transformations in cobalt-based OER catalysts and establish EQCM-D as a sensitive operando technique for probing electrocatalyst transformations.
Keywords: electrocatalysis; Co3O4; EQCM-D; OER

The Handbook of Qualitative and Quantitative Content Analysis - Schneijderberg, Christian; Wieczorek, Oliver; Steinhardt, Isabel
Translated from German, The Handbook of Qualitative and Quantitative Content Analysis is a comprehensive handbook which offers an application-orientated introduction to qualitative and quantitative content analysis methods. The book provides explanations for beginners from bachelor level onwards on how to select an appropriate qualitative or quantitative content analysis method and how to use the chosen method(s) depending on research interest and amount of data. Part 1 defines the basics of qualitative and quantitative content analysis and empirical research, including research quality conventions and how to do interpretation; Part 2 is a practical guide to classical qualitative content analysis and semi-automated quantitative content analysis; and Part 3 introduces Python alongside automated techniques such as correspondence analysis, semantic network analysis, sentiment analysis, and topic modelling using generative and deep learning algorithms. Each of these sections are enriched with extensive examples and cover a range of software applications, including AntConc, MAXQDA, Python, and VosViewer. This is the ideal resource for anyone interested in content analysis research methods across the social sciences, humanities, and data sciences.

Erbwort oder Buchwort? Decoding the Disciplines in Romanistikseminaren - Kunert, Irene Dorothea (die hochschullehre)

An Axiomatization of the Banzhaf Index to Measure Influence in Qualitative Comparative Analysis - Haake, Claus-Jochen; Schneider, Martin (International Journal of Game Theory)
The Banzhaf power index can be used to quantify the explanatory power of single conditions in a configurational analysis that aims at identifying whether combinations of conditions are sufficient for an outcome. The latter method is an integral part of the Qualitative Comparative Analysis (QCA) approach. It is widely used in the literature, e.g., in the field of International Management. Haake and Schneider (2023) give a rigorous description of the connection between the empirical and game theoretic modeling. To justify that the Banzhaf index is an appropriate tool to measure the influence of a condition, this paper discusses a novel axiomatization of the Banzhaf index that uses axioms that are directly linked to the QCA methodology. As a side result, we demonstrate that in our model the Banzhaf index can be reinterpreted as an average of Shapley-Shubik indices.
Keywords: Banzhaf index; axiomatization; QCA; explanatory power

A modified Levenberg–Marquardt method for estimating the elastic material parameters of polymer waveguides using residuals between autocorrelated frequency responses - Itner, Dominik; Dreiling, Dmitrij; Gravenkamp, Hauke; Henning, Bernd; Birk, Carolin (Mechanical Systems and Signal Processing)
In this contribution, we address the estimation of the frequency-dependent elastic parameters of polymers in the ultrasound range, which is formulated as an inverse problem. This inverse problem is implemented as a nonlinear regression-type optimization problem, in which the simulation signals are fitted to the measurement signals. These signals consist of displacement responses in waveguides, focusing on hollow cylindrical geometries to enhance the simulation efficiency. To accelerate the optimization and reduce the number of model evaluations and wait times, we propose two novel methods. First, we introduce an adaptation of the Levenberg–Marquardt method derived from a geometrical interpretation of the least-squares optimization problem. Second, we introduce an improved objective function based on the autocorrelated envelopes of the measurement and simulation signals. Given that this study primarily relies on simulation data to quantify optimization convergence, we aggregate the expected ranges of realistic material parameters and derive their distributions to ensure the reproducibility of optimizations with proper measurements. We demonstrate the effectiveness of our objective function modification and step adaptation for various materials with isotropic material symmetry by comparing them with the Broyden–Fletcher–Goldfarb–Shanno method. In all cases, our method reduces the total number of model evaluations, thereby shortening the time to identify the material parameters.
Keywords: Material parameter estimation; Waveguide; Nonlinear optimization; Inverse problem; Least squares

Approximating Incoherent Monochromatic Light Sources in FDTD Simulations - Metzner, Dominik; Potthoff, Jens; Zentgraf, Thomas; Förstner, Jens (Photonics)
Light-emitting diodes (LEDs) are becoming increasingly important across various sectors of the lighting industry and are being used more frequently. In the field of symbolic projection, research is increasingly focusing on implementing light modulation using energy-efficient, incoherent LEDs rather than lasers. Since light modulation in micro- and nano-optics is typically achieved through phase modulation, Finite-Difference Time-Domain (FDTD) simulations are employed for analysis. The objective of this article is to investigate different approaches for approximating incoherent monochromatic light sources within FDTD simulations. To this end, two approaches based on dipole sources are considered, as well as a method involving plane waves with modulated wavefronts based on Cosine–Fourier functions and a method based on the superposition of Gaussian beams. These methods are evaluated in terms of their accuracy using a two-dimensional double-slit configuration and are compared against a fully incoherent analytical reference.
Keywords: tet_topic_opticalantenna; tet_topic_numerics; tet_topic_meta

Proton-Conducting Sulfonated Periodic Mesoporous Organosilica - Wagner, Tobias; Tiemann, Michael (Nanomaterials)
Proton exchange membranes (PEMs) are essential for fuel cells, yet conventional materials like Nafion suffer from humidity dependence and limited thermal stability. This study introduces sulfonated phenylene-bridged periodic mesoporous organosilicas (PMOs) as promising inorganic–organic hybrid PEMs, synthesized via surfactant-templating with varying alkyl chain lengths for different mesopore sizes. Post-synthetic functionalization involves nitration of phenylene moieties, reduction to amines, and ring-opening of propane or butane sultones to graft sulfonic acid groups via flexible spacers, achieving homogeneous distribution along pore walls. Post-functionalization is confirmed by powder X-ray diffraction (PXRD), revealing preserved 2D hexagonal p6mm ordering and phenylene stacking. N2 physisorption shows type IV isotherms with reduced pore volumes and pore sizes. 1H NMR is used to quantify functionalization degrees. Impedance spectroscopy on pressed pellets demonstrates proton conductivities up to 2 × 10−3 S cm−1 at 30 °C and 90% RH, depending on the functionalization degree, confirming sulfonic acid-mediated conduction.

Langrezension zu James McElvennys 'Entstehung und Entwicklung der modernen Linguistik. Von den Anfängen bis zum Zweiten Weltkrieg' - Markewitz, Friedrich (Zeitschrift für Angewandte Linguistik)

Selbstgesteuertes Lernen, Partizipation und das 4K-Modell. Lehre in der Kultur der Digitalität - Hallmann, Nicole; Mahs, Marie; Grant , Lloyd-Spencer; Baier, Marla Ricarda; Cerezo Alarcon, Alina Luisa; Kepper, Florian; Steinhardt, Isabel (die hochschullehre)

Higher accuracy with fewer projections? Automated scan angle selection for dimensional Computed Tomography based on a simple data completeness measure for the part surface - Butzhammer, Lorenz; Braun, Matthias Robert Oskar; Herath, Colin; Hausotte, Tino (e-Journal of Nondestructive Testing)
Selecting scan angles such that surface segments are aligned with straight X-ray paths (i.e., rays are tangential to the surface and therefore perpendicular to the local surface normal) is known to produce sharper transitions of those surface segments in the reconstructed volume. This enhances dimensional accuracy in sparse-view computed tomography (CT). However, existing approaches offer no direct means to exploit this criterion for automatic scan-angle optimization. We propose a method that uses a virtual representation of the CT setup, including an STL surface model of the inspected part, to automatically identify taskspecific scan angles. Using elementary vector calculus, the algorithm determines projection directions that generate tangential X-rays for targeted surface segments. To support different levels of geometric complexity, we introduce two variants of the angle-selection procedure. The methods were experimentally validated on two objects with distinct absorption and geometric characteristics. For a steel gauge block, employing the minimum number of task-specific projections required for surface-data completeness substantially outperformed a conventional high-projection scan. For a geometrically more complex test object, surface-related errors were still reduced within the region of interest. The proposed approach – particularly suited for flat surface structures and not accounting for image-degrading factors other than cone-beam artifacts – shows promise for high-throughput dimensional metrology of mono-material parts.

Role of Defects in Reversible Surface Restructuring and Activity of Co3O4 Oxygen Evolution Electrocatalysts - Scharf, Carl Hendric; Chandraraj, Alex; Dyk, Konrad; Stebner, Felix; Lepin, Sören; Tian, Jing; El Bergmi Byaz, Laila; Stettner, Jochim; Leppin, Christian; Kotova, Anastasiia; Reinke, Sebastian; Linnemann, Julia; et al. (ACS Catalysis)
Overcoming the slow kinetics of the oxygen evolution reaction at the anode is a key challenge for the production of hydrogen via electrolysis. This reaction operates at very positive potentials, where the electrocatalyst is exposed to highly oxidative conditions and prone to potential-dependent transformation of the near-surface region. While substantial evidence for such surface restructuring exists, its extent and relevance for the catalyst’s activity are unclear. We address this topic for the case of Co3O4, one of the best-known electrocatalysts exhibiting surface restructuring, by studies of epitaxial (111)-ordered electrodeposited films with combined operando X-ray surface diffraction and absorption spectroscopy, electrochemical impedance spectroscopy, and electrochemical measurements on rotating disk electrodes. Comparison of the as-prepared and annealed state of the same samples, which both are stable even under long-term oxygen evolution conditions, provides clear insight into the role of surface defects. Our results show that defect-free annealed Co3O4(111) surfaces are structurally stable over a wide potential range and hydroxylate via adsorption at surface oxygen and Co sites. Potential-induced surface restructuring of the Co3O4 lattice occurs only in the presence of surface defects, leading to the formation of the well-known nanometer-thick oxyhydroxide skin layer. The presence of this skin layer promotes oxygen evolution at low overpotentials but results in higher Tafel slopes. As a result, highly ordered Co3O4(111) surfaces are more active at high current densities than defective Co3O4 surfaces that undergo surface restructuring. These results highlight that strategies for catalyst surface defect engineering need to be application-oriented.
Keywords: electrocatalysis; oxygen evolution reaction; cobalt spinel; operando characterization

Zwischen Förderkonzept und Vorschrift – Eine empirische Studie zur Praxis der Förderplanung an Schulen in Nordrhein-Westfalen - Neumann, Phillip; Bunte, Charline; Melzer, Conny (Zeitschrift für Heilpädagogik)
Obwohl Förderpläne schon seit den 1990er Jahren umgesetzt werden, es mittlerweile recht viele Publikationen mit Beschreibungen des Konzepts Förderplanung gibt und diese in allen Bundesländern Deutschlands rechtlich für Schülerinnen und Schüler mit einem festgestellten Bedarf an sonderpädagogischer Unterstützung vorgeschrieben sind, gibt es recht wenige empirische Studien über die tatsächliche Umsetzung in der Praxis. Dieser Beitrag möchte die große Lücke schließen, indem die Praxis der Förderplanung an Allgemeinen Schulen und an Förderschulen in Form einer digitalen Befragung in NRW in den Blick genommen wird. Insbesondere die Frage, wie und in welcher Form Förderpläne erstellt, umgesetzt, evaluiert und fortgeschrieben werden, steht im Mittelpunkt dieser Studie. Zentrale Ergebnisse zeigen, dass Förderpläne zwar i.d.R. aufgrund der rechtlichen Vorschrift erstellt werden, aber auch für die Strukturierung des Förderprozesses fachlich-inhaltlich genutzt werden. Hierbei wird deutlich, dass von den Allgemeinen Schulen eher die Grundschulen Förderpläne auch im weiteren fachlichen Sinn nutzen. Es wird aber auch deutlich, dass einige der befragten Schulen Förderpläne gezielt nutzen, um ein Feststellungsverfahren zu eröffnen und Ressourcen zu generieren und Förderpläne damit auch defizitorientierter schreiben als im Falle der fachlichen und inhaltlichen Strukturierung von Förderprozessen.
Keywords: Sonderpädagogik; Inklusion; Sonderpädagogische Förderung; Förderplanung; Förderpläne; Kooperation

Towards Automated DNS Censorship Circumvention - Lange, Felix; Niere, Niklas; Somorovsky, Juraj
Censorship is employed by many governments and ISPs worldwide, with an increasing trend in recent years. One of the most censored protocols is DNS: censors target unencrypted and encrypted DNS to prevent clients from resolving the domain name of unwanted websites. Despite much research on DNS censorship, only a few tools can circumvent it.To support users affected by DNS censorship, we present DPYProxy-DNS, a DNS resolver that automatically detects and employs a working DNS censorship circumvention. We demonstrate the effectiveness of DPYProxy-DNS by automatically circumventing DNS censorship in China and Iran and analyzing DNS censorship mechanisms in these countries. Our analyses re veal that DNS censorship in Iran is ineffective against encrypted DNS. In China, DPYProxy-DNS revealed two consistently working circumvention techniques for unencrypted DNS: TCP segmentation for DNS over TCP and ignoring DNS responses injected by the Great Firewall of China (GFW). Our findings reveal varying levels of DNS censorship across different countries, underscoring the importance of the automated circumvention approach we provide with DPYProxy-DNS.

New Quick And Easy Publication - Will be edited by LibreCat team - Orlando Massopo (Quick And Easy Journal Title)

Postdigitale Musikpädagogik im Plattformzeitalter. Über die konzeptionelle Rahmung einer Fortbildung für Lehrkräfte zur Rolle audiovisueller Kunst- und Vermittlungspraxis in postdigitaler Musikkultur - Godau, Marc; Gosmann, Phillip (Diskussion Musikpädagogik)